Introduction to instrumentation and measurements - Northrop, Robert B., 1935-2019 (Boca Raton : Taylor and Francis, 2005)
Measurement Systems. Analog Signal Conditioning. Noise and Coherent Interface in Measurements. DC Null Measurement. AC Null Measurements. Survey of Sensor Input Mechanisms. Applications of Sensors to Physical Measurements. Basic Electrical Measurements. Digital Interfaces in Measurement Systems. Introduction to Digital Signal Conditioning. Examples of the Design of Measurement Systems. References and Bibliography.
Keywords: Elektrische meetinstrumenten